2002
DOI: 10.1007/s00374-002-0490-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cadmium contamination with sewage sludge and phosphate fertiliser amendments on soil enzyme activities, microbial structure and available cadmium

Abstract: The effect of Cd pollution (50 mgkg -1 ), with and without sewage sludge (Sw) and phosphate fertiliser (P) addition on soil biochemical activity and available Cd was assessed in a 112 day soil incubation experiment. The availability of Cd decreased with incubation time and was reduced by the sludge and P additions resulting in the following order, Cd>P+Cd>Sw+Cd. With the exception urease and NAGase activities, all other enzyme activities were negatively correlated with available Cd. The total culturable bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 32 publications
3
22
0
1
Order By: Relevance
“…Also, ASA had a significant negative correlation with total Cu content, and APA had significant negative correlations with total Ni and Fe contents (P<0.05). Several studies demonstrated that enzyme activities decreased with increasing heavy metal concentrations (Karaca et al 2002;Kızılkaya 2004). Tyler (1974) found that there were approximately straight regression lines between enzymatic activity or respiration rate and log Cu+Zn concentration, with highly significant negative regression coefficients for urease and acid phosphatase activity as well as respiration rate.…”
Section: Resultsmentioning
confidence: 97%
“…Also, ASA had a significant negative correlation with total Cu content, and APA had significant negative correlations with total Ni and Fe contents (P<0.05). Several studies demonstrated that enzyme activities decreased with increasing heavy metal concentrations (Karaca et al 2002;Kızılkaya 2004). Tyler (1974) found that there were approximately straight regression lines between enzymatic activity or respiration rate and log Cu+Zn concentration, with highly significant negative regression coefficients for urease and acid phosphatase activity as well as respiration rate.…”
Section: Resultsmentioning
confidence: 97%
“…1). Also and according to Karaca et al (2002), phosphatase activity decreased when Cd increased in soil. However the results obtained in the urease and β-glucosidase activities are not in agreement with other authors.…”
Section: Discussionmentioning
confidence: 92%
“…Soil microbial growth and enzyme activities are affected by high concentrations of Cd (Moreno et al, 1999;Landi et al, 2000;Karaca et al, 2002;Moreno et al, 2006). The normal concentration of Cd in soils is between 0.1 and 1.0 mg kg − 1 .…”
Section: Introductionmentioning
confidence: 98%
“…The protease activity has the function to catalyze the hydrolysis of protein-N, giving rise to a mixture of amino acids which in turn decompose to ammonium-N (ammonification reaction), available to plants and microorganisms (Karaca et al, 2002), or are oxidized to nitrate (nitrification reaction); no significant treatment effects were observed on the enzyme activity. These results disagree with those of Melo (2006), who reported increased protease activity in two Oxisols treated with increasing SS rates up to 60 t ha -1 (SS from Barueri, State of São Paulo).…”
Section: Resultsmentioning
confidence: 99%